Court orders against express trustees - Williams, S (2019)
This thesis concerns five court orders: the Surcharging Order, Subject-Matter Distribution Order, Lesser Receipt Order, Falsification Order, and Personal Loss Order. This thesis considers two questions, one descriptive and one normative. The descriptive question asks whether these five orders are available as a matter of law in England and Wales. The normative questions asks whether there are normative reasons for or against the making of such orders. These questions are considered in respect of express trustees of trusts for persons following breach of the duty to follow the settlor’s communicated intentions, and breach of the duty of care.